A Phenomenological Study of the Lived Experiences of the Generation X and Y Entrepreneurs (Sinergi : Jurnal Ilmiah Ilmu Manajemen, 2017)
This qualitative phenomenological approach examined the Generation X and Y cohorts in terms of their lived experience towards the  entrepreneurial journey in Singapore, which can consequently fill empirical gap on entrepreneurship among generational cohorts of Asian entrepreneurs.  The study sample comprised  15 generation X and 15 Y Singaporean entrepreneurs from 30 companies who identified their involvement in starting a business venture and in the day-to-day running of the business. Using NVIVO to cull down key components and ideas from the data, the study revealed that Generation X and Generation Y to have similar work attitudes, values and behaviours. The differences between the generations include differences in age, experience as well as obligations in life such as to one’s family. Further studies are needed to examine the differences of these cohorts in terms demographic, psychological and social variables to provide additional insights and identify contributing factors to successful entrepreneurial venture.